2011
DOI: 10.1017/s136898001100111x
|View full text |Cite
|
Sign up to set email alerts
|

Does consuming breakfast influence activity levels? An experiment into the effect of breakfast consumption on eating habits and energy expenditure

Abstract: Objective: To experimentally compare the effects of eating or skipping breakfast on energy expenditure, activity levels and dietary habits. Design: A randomised cross-over trial, lasting 2 weeks. Participants were provided breakfast during one week and were required to fast until mid-day during the other week. Setting: University campus. Subjects: Forty-nine participants (twenty-six female and twenty-three male participants) were recruited. Food intake was monitored using food diaries, and energy expenditure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
52
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 47 publications
6
52
0
2
Order By: Relevance
“…15 However, some research14,16 did not report the participants' breakfast habits, and this could be of relevance as differences in BMI between breakfast eaters and skippers are possibly associated with differing morning habits. 17 Such habits may in turn be linked to a preference for early or late rising and being more active earlier or later in the day, respectively; these patterns have been considered by researchers by reference to the concept of 'morningness',18 and these time of day preferences may be linked to caffeine intakes. Several studies19,20 have shown that people who prefer to be active in the evening consume more caffeine compared with those who are morning active.…”
Section: Introductionmentioning
confidence: 99%
“…15 However, some research14,16 did not report the participants' breakfast habits, and this could be of relevance as differences in BMI between breakfast eaters and skippers are possibly associated with differing morning habits. 17 Such habits may in turn be linked to a preference for early or late rising and being more active earlier or later in the day, respectively; these patterns have been considered by researchers by reference to the concept of 'morningness',18 and these time of day preferences may be linked to caffeine intakes. Several studies19,20 have shown that people who prefer to be active in the evening consume more caffeine compared with those who are morning active.…”
Section: Introductionmentioning
confidence: 99%
“…throughout the day suggested that breakfast omission leads to greater energy intake than breakfast 255 consumption (35) . Two recent studies from the same research group using similar cross-over consumed an ad libitum high-carbohydrate breakfast under supervised laboratory conditions (36) .…”
mentioning
confidence: 99%
“…Other past studies have attempted to quantify aspects of physical activity behaviour in breakfast or fasting (36,48) or any difference in accelerometer counts when comparing a three-meal 354 feeding pattern with a single evening-meal for 8 weeks (61) . However, natural adjustments in 355 overall activity may have been masked in the latter study because participants were "encouraged 356 to maintain their normal exercise throughout the day".…”
mentioning
confidence: 99%
“…Although we did not include breakfast skipping as a separate group, our data provides some information to explain the previous conflicting results that eating versus skipping breakfast was associated with similar (22,23) , higher (8,24) , or lower (5) daily energy intake. We found that energy consumed at breakfast is positively associated with daily energy intake at the higher quartiles (Q3, Q4), but not the lower quartiles (Q1, Q2) of breakfast energy.…”
Section: Discussionmentioning
confidence: 99%